Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fphar.2020.00783
|View full text |Cite
|
Sign up to set email alerts
|

Primary Non-Adherence to Antihistamines—Conclusions From E-Prescription Pilot Data in Poland

Abstract: Background: In allergic conditions such as allergic rhinitis and urticaria, orally administered H 1 -antihistamines belong to first-line therapy and therefore, are widely prescribed. Due to the frequent, and often chronic, course of allergic diseases, adherence is of great importance. In 2018 a novel, nationwide e-prescription system was piloted in Poland, which allowed to analyze primary non-adherence to orally administered H 1 antihistamines.Objectives: To assess the primary non-adherence to orally administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…The actual degree of drug use is modified by patient adherence, which varies from over-to underuse of prescribed drugs. Fortunately, the data analyzed by us, i.e., dispensation data, are not biased by primary non-adherence, which was recently found, in other studies conducted by our group, to reach the overall level of 20.8% (Kardas et al, 2019), with some drug groups reaching even higher values (e.g., 31.3% in antihistamines (Kardas et al, 2020)). On the other hand, real-world drug use is affected by secondary non-adherence, which in Poland in some cases reached the level of over 80% (Kardas, 2011).…”
Section: Discussionsupporting
confidence: 59%
“…The actual degree of drug use is modified by patient adherence, which varies from over-to underuse of prescribed drugs. Fortunately, the data analyzed by us, i.e., dispensation data, are not biased by primary non-adherence, which was recently found, in other studies conducted by our group, to reach the overall level of 20.8% (Kardas et al, 2019), with some drug groups reaching even higher values (e.g., 31.3% in antihistamines (Kardas et al, 2020)). On the other hand, real-world drug use is affected by secondary non-adherence, which in Poland in some cases reached the level of over 80% (Kardas, 2011).…”
Section: Discussionsupporting
confidence: 59%
“…The prevalence of PNA is consistent with what has been documented in other studies of PNA in dermatology patients. 2,11 Primary non-drug adherence was noted more in females. This may be because there were more females than males in the study in keeping with females being reported to attend clinics more than males.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, a younger age has been linked to PNA. 2,10,11,15 Moo-Young et al did not find age to be associated with PNA. 5 Moo-Young et al specifically looked at distance to the pharmacy as a risk for PNA in the United States of America where a means of transportation is not a problem and pharmacies are located in the neighbourhoods.…”
Section: Limitationsmentioning
confidence: 93%
See 1 more Smart Citation
“…The non‐adherence to these drugs was lower than obtained in our previous study on drivers of general non‐adherence in Poland, where for drugs in 6 major areas (antidiabetic, antithrombotic, cardiovascular, cholesterol medications, antibiotics and psychiatric drugs) the primary non‐adherence was 20.8% [31 ]. Also, it was lower than of that for antihistamine drugs, for which the level of primary non‐adherence was 21% [32 ].…”
Section: Discussionmentioning
confidence: 99%